Challenges and opportunities for a CAMPEP-accredited medical physics graduate program. (August 2018) - Kleefeld, Christoph; Foley, Mark
Abstract : A long running MSc in Medical Physics program, delivered by a close university – hospital collaboration, was awarded CAMPEP accreditation in 2015. This presentation will give an outline of the current program structure and will identify challenges likely affecting the areas of teaching, research and course administration. Strategies to address these challenges will be discussed. Challenges evolve from the accreditation itself, the adjustment of the existing course curriculum where modules were only partially compliant, from the transposition of the EU council directive into Irish law, and from policies of the host university. Since the accreditation the number of students enrolled in the program increased from 8 in 2015/16 and 16 in 2016/17 to 21 in 2017/18. The number of non-EU students in these cohorts was 2, 5, and 4, respectively. The total number of applicants averages at approximately 50 per year. A further increase in student intake has been advocated but might impact negatively on the quality of the clinical training which forms a vital part of the program. Students are given access to clinical systems for laboratory exercises as well as for pursuing research projects, gaining some clinical experience which will increase their employability. However, local clinical access has to be limited. In order to mitigate the situation, the program cooperates with medical physics departments nationwide, thus contributing to an active Irish research landscape. A related issue, the mismatch between the number of available residency positions and the number of graduates, will be further expanded on.